Impact of hyaluronic acid-modified hafnium metalorganic frameworks containing rhynchophylline on Alzheimer’s disease - Lin Shiguo; Ye Yanshan; Lin Sujin (Open Life Sciences)
Rhynchophylline (Rhy) is an attractive candidate, harboring ameliorative effects on Alzheimer’s disease (AD). Nevertheless, its application is impeded by its low water solubility and poor bioavailability. Here we synthesized and characterized the Rhy-loaded hyaluronic acid-modified hafnium metal-organic frameworks (HA@Rhy@Hf-MOF). The drug release profiles of free Rhy from HA@Rhy@Hf-MOF were evaluated, and the cellular toxicity was assessed through Cell Counting Kit-8 (CCK-8) assay. In vivo experiments included behavioral experiments of various murine capabilities, with neuronal damage appraised through Hematoxylin and Eosin staining and Nissl staining. Subsequently, the formation of AD-related amyloid beta (Aβ) plaques formation and Tau phosphorylation were measured. The HA@Rhy@Hf-MOF with spherical shape were presented as uniformly dispersed and with a negative charge, exhibiting a pronounced pharmacological sustained-release effect and minimal cellular toxicity. Findings from the Morris water maze test, novel object recognition test, and elevated plus maze test substantiated that HA@Rhy@Hf-MOF effectively mitigated cognitive deficiency and anxiety, and enhanced spatial learning in AD mice. Immunofluorescence staining and Western blot both illustrated that HA@Rhy@Hf-MOF could attenuate hippocampal Aβ formation and deposition, as well as tau hyperphosphorylation. In conclusion, HA@Rhy@Hf-MOF exerts its therapeutic efficacy against AD by targeting the deposition of Aβ plaques and inhibiting site-specific phosphorylation of Tau.